A model for the analysis of the structural failure of the clay core in rockfill dams due to overtopping - Ricoy, L. F., author; Toledo, M. Á., author; Morán, R., author; Colorado State University. Department of Engineering, publisher (Colorado State University. Libraries, 2016)
In 2014 the Dam Safety Research Group (SERPA) of the Technical University of Madrid performed several tests to assess the behavior of rockfill dams in overtopping scenarios. A structural failure pattern of the clay core was observed, as expected. Hence, it was concluded that a model to simulate the observed failure mechanisms was needed. The model described herein provides the first results on assessment of the clay core stability following failure of the downstream shell. The failure process may result in one or more brittle and abrupt breakage phases of the core, herein classified as structural breakages, as opposed to the progressive failure caused by the erosion of the cohesive material. Thus, total or partial failure of the clay core occurs when the acting forces reach one of the instability conditions: overturning or sliding. The model was utilized to retroactively analyze two experiments carried out in the laboratory; the results obtained were consistent with the experimental measurements. The model is based on simple mechanical principles, but represents a paradigm shift in the interpretation and evaluation of the overtopping failure processes, especially since it results in a failure hydrograph different from those typically adopted, and therefore, has repercussions in the development of emergency plans.
Presented at the Protections 2016: 2nd international seminar on dam protection against overtopping: concrete dams, embankment dams, levees, tailings dams held on 7th-9th September, 2016, at Colorado State University in Fort Collins, Colorado, USA. The increasing demand for dam and levee safety and flood protection has motivated new research and advancements and a greater need for cost-effective measures in overtopping protection as a solution for overtopping concerns at levees and dams. This seminar will bring together leading experts from practice, research, development, and implementation for two days of knowledge exchange followed by a technical tour of the Colorado State University Hydraulic Laboratory with overtopping flume and wave simulator. This seminar will focus on: Critical issues related to levees and dams; New developments and advanced tools; Overtopping protection systems; System design and performance; Applications and innovative solutions; Case histories of overtopping events; Physical modeling techniques and recent studies; and Numerical modeling methods.
Keywords: dam failure; overtopping; rockfill dam; clay core